2011
DOI: 10.1063/1.3537828
|View full text |Cite
|
Sign up to set email alerts
|

Structure evolution of Zn cluster on graphene for ZnO nanostructure growth

Abstract: Monte Carlo simulations are carried out for Zn cluster supported on a suspended graphene to estimate the morphological evolution of the following growth of ZnO nanostructure. The metalmetal interactions are modeled with the tight-binding many-body potential and a Lennard-Jones potential is used to describe the metal-carbon interactions. The dynamic processes of Zn cluster in the temperature field decomposing and drifting effects are visualized through the simulation. Zn atoms make one regular atomic single lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…5(a). Zn cluster is easily structured and grows over MLG substrate because Zn atoms produce one orderly atomic layer on last grapheme layer and they form orderly nucleation sites for the following crystal growth (Guo et al, 2011). It has been demonstrated that the Zn buffer layer played an important role in the improvement of crystal quality of ZnO films (Fu et al, 1998).…”
Section: Growth Mechanismmentioning
confidence: 99%
“…5(a). Zn cluster is easily structured and grows over MLG substrate because Zn atoms produce one orderly atomic layer on last grapheme layer and they form orderly nucleation sites for the following crystal growth (Guo et al, 2011). It has been demonstrated that the Zn buffer layer played an important role in the improvement of crystal quality of ZnO films (Fu et al, 1998).…”
Section: Growth Mechanismmentioning
confidence: 99%
“…However, the metal atoms are weakly absorbed in contrast to the adatoms when they supported on a pristine Si substrate. It is reasonable to postulate that the LJ potential is sufficient for a qualitative study of the evolution of Zn cluster on the Si substrate [25,26]. As already well known, graphene has a sp 2 hybrid carbon network.…”
Section: Computational Methodologymentioning
confidence: 98%
“…To initialize the fitting procedure, the interatomic interactions between the atoms of the ZnO slab and the atoms of the CH 3 OH bulk are described with an LJ-FF (see eq ) and OPLS mixing rules. Therefore, we use the values for ε and σ for Zn and O ZnO from the literature , (see the Supporting Information). During the fitting procedure of the interfacial FF, an Ahlrichs–Penco–Scoles (APS)-FF with the functional form is parameterized resulting in five parameters.…”
Section: Methodsmentioning
confidence: 99%